Métodos para avaliação da qualidade fisiológica de sementes de azevém anual (Lolium multiflorum Lam.) - Silva, Janaína Iara (2012)
The methods available to characterize the quality of forage seeds of temperate climate are not very specific, and mostly used are those adapted for the seeds of the most crops, which has led to achieving results and little disform reliable. This study aimed to seek the establishment of methodologies to assess accurately the quality of different seed lots of annual ryegrass. For that were tested methodological variations of tests commonly used for other crops seeds and evaluated the performance of an alternative method, trying to detect an alternative that would allow better demonstrate the physiological field and seed storage. We used annual ryegrass, represented by four lots. Seeds were evaluated using the tests for determining the water content, physical purity, thousand seed weight, germination, first count germination, accelerated aging and electrical conductivity, seedling emergence in sand tray, rate of emergence (IVE). According to the results, we concluded that the electrical conductivity test is promising for evaluating the effect of annual ryegrass. The use of combination 100 seeds/25mL the electrical conductivity test, allows the separation of lots at different levels of force. You can determine the effect of annual ryegrass seeds by accelerated aging test using 41ºC/48h and 42ºC/72h.